Framework for understanding public pluralities in greenspace design and consultation - Ngoc Thuy Nguyen; Alexandra M. Collins; Catherine Matilda Collins (npj Urban Sustainability)
Abstract Public participation underpins contemporary governance, facilitating discourse, enhancing decision legitimacy, and improving outcomes. In urban greenspace planning, however, persistent barriers, including cultural disparities and tokenism, impede effective engagement. Traditional assumptions of a homogeneous ‘public’ and uncritical endorsement of participation’s merits overlook group heterogeneity. Acknowledging public plurality is essential for authentic involvement. Within environmental science, scant research addresses public segmentation to devise bespoke, inclusive strategies. This study innovatively integrates Situational Theory of Public and Self-Determination Theory to examine diverse public segments in green space consultation and design. A UK-based survey classified four segments (active, aware, latent, non-public) and linked them to motivational drivers: trust, recognition, cohesion, employing ANOVA and PCA. Results reveal uniform approaches are inadequate. Autonomy-supportive contexts and community bonds outweigh generic incentives. Extrinsic rewards prove secondary to intrinsic factors. This framework offers practitioners a tool to tailor engagement, optimising greenspace outcomes across diverse populations.